Settlement of Disputes Regarding Wakaf Land Claimed by Parties Who Are Not the Heirs - Zilah, Noor (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2026)
The practice of land waqf without a Deed of Waqf Pledge (AIW) often faces legal disputes, particularly when non-heirs claim the waqf land and consider it part of the inheritance. Previous research has focused on the AIW as an administrative requirement for waqf validity. However, they have not sufficiently addressed the legal status of waqf without an AIW and how judges prove the substance of the waqf in disputes involving non-heirs. This study aims to analyze the legal status of waqf land without an AIW and examine the legal considerations of the panel of judges in the Lubuk Pakam Religious Court Decision Number 1634/Pdt.G/2024/PA.Lpk. The method used is normative legal research with a statutory approach and case studies. This research utilizes primary and secondary legal materials, including waqf regulations, legal doctrine, and court decisions. The results of the study show that the panel of judges emphasized substantive evidence related to the designation and social function of waqf land through the consistency of witness statements and facts of control and use of land for public interests, even though the waqf was not supported by AIW. The court rejected the defendants' ownership claim because they lacked legal standing as legal heirs. This research contributes to strengthening the doctrine that the legal status of waqf is not solely determined by administrative formalities, and affirms the position of the Deed in Lieu of Waqf Pledge as a crucial instrument in providing preventive and repressive legal protection against unilateral claims by non-heirs.